2006
DOI: 10.1080/10934520600966284
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Approach for Leachate Treatment: Electricity Generation in Microbial Fuel Cell

Abstract: Electricity generation from landfill leachate was examined by using both a dual-chamber microbial fuel cell (MFC) and a single chamber MFC. Experimental results showed that the maximum power density of 2060.19 mW/m3 in the dual-chamber MFC and that of 6817.4 mW/m3 in the single chamber MFC were obtained. It was recognized that the difference in internal resistance for two MFC systems was the main reason for resulting in the difference of power generation. Power generation as function of chemical oxygen demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 22 publications
0
38
1
3
Order By: Relevance
“…Hence, 95 % of the substrate was not employed to generate electricity. According to You et al, (2006), low electron recovery efficiency could be due to improper selection of exoeletrogenic bacteria from a microbial community as a result of an inadequate culture medium or environmental conditions. This selection could involve appropriate control of the nutrients during MFC operation.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, 95 % of the substrate was not employed to generate electricity. According to You et al, (2006), low electron recovery efficiency could be due to improper selection of exoeletrogenic bacteria from a microbial community as a result of an inadequate culture medium or environmental conditions. This selection could involve appropriate control of the nutrients during MFC operation.…”
Section: Resultsmentioning
confidence: 99%
“…Cathodic and anodic potentials were also measured occasionally against a Calomel reference electrode. To determine the MFC current and power, external loads in the range 1,000-6,000 ohms resistors [36] were applied during the biodegradation of organics. Sufficient time was given for the potential to stabilize.…”
Section: Analysesmentioning
confidence: 99%
“…However, few studies involving high concentration organic wastewater as substrates have been reported. 16 The high concentration organic wastewater may provide high chemical energy compared with low COD biodegradable sanitary sewage. In principal, if suitable bacteria are directly used to catalyze the effective conversion of organic matter into electricity without the addition of mediators, a much higher power output can be obtained.…”
Section: Introductionmentioning
confidence: 99%